Impact of ripening periods on the key volatile compounds of Cheddar cheese evaluated by sensory evaluation, instrumental analysis and chemometrics method - Li-Qin You; Yong-Rui Wang; Shuang Bai; Xue-Yao Wang; Zhao-Jun Wei (Applied Food Research)
We examined the impact of varying ageing times (0, 6, 12, and 15 months) on the alterations in the concentration of key volatile compounds in Cheddar cheese as it ripened. With PCA of E-nose and PLS-DA of gas GC–MS and GC-IMS, the cheddar cheese samples could be identified from one another. As the cheese samples ripened longer, their overall acid, ester, and aldehyde concentrations increased. The important flavor biomarkers of ripened Cheddar cheese were 1-hexanol, 1-octen-3-ol, 2,6-dimethylpyrazine, octanal, decanal, 1-pentanol, butanoic acid ethyl ester, (E)-2-octenal, nonanoic acid, hexanal, dimethyltrisulfide, (E)-2-undecenal, and 1-heptanol, according to chemometric methods. The cheese samples that were ripened for 0 and 6 months showed a considerable contribution of the milky flavor. There was a strong negative association between the milky flavor and acetic acid. The aged Cheddar cheese exhibited distinct nutty, sour, and fruity flavors after 12 and 15 months. The fruity flavor was highly positively correlated with hexanal, octanal, and 2-heptanone, butanoic acid, ethyl ester, and acetic acid. The sour and nutty flavors were also strongly positively correlated with acids, while the sour and nutty flavors were positively influenced by ethyl hexanoate and benzaldehyde. This study provides data on the composition and variations in the flavor profile of ripening cheddar cheese.